Pengaruh Kemampuan Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Pengadilan Agama Tais Kelas II Kabupaten Seluma - Sandy Septe Anugrah; Ida Ayu Made Gayatri; Yesi Indian Ariska (Jurnal Multidisiplin Dehasen (MUDE), 2023)
Institution must try to encourage its employees to work well so that they can achieve the best performance. To create high employee performance, of course, there are several things that must be considered by the agency, such as work ability and work motivation. The purpose of this study is to determine the effect of work ability and work motivation on employee performance at Tais Religious Court Class II of Seluma Regency. The sample in this study was 33 employees at Tais Religious Court Class II, of Seluma Regency. The data collection used a questionnaire and the analytical method used is multiple linear regression, determination test and hypothesis testing. The results of multiple linear regression calculations obtained multiple linear regression equation Y = 8.650+0.334X1+0.478X2. The coefficient of determination of the Adjusted R square value is 0.455. This means that X1 (work ability), and X2 (work motivation) affect employee performance (Y) by 45.5% while the remaining 54.5% is influenced by other variables not examined in this study. The results of F test show that the significance is 0.000 <0.05. Because the significance level is below 0.05, it shows that X1 (work ability) and X2 (work motivation) have a positive and significant effect on employee performance (Y). Work ability has a positive and significant effect on employee performance because the significant value is 0.041 < 0.05, work motivation has a positive and significant effect on employee performance because the value is 0.007 < 0.05.